Identification of Resistant Biotypes of Leptochloa chinensis in Rice Field and their Control with Herbicides - Motior Rahman, M.; Ismail, S.; Sofian-Azirun, Mohd (Academic Journals, 2011)
Weed populations of sprangletop (Leptochloa chinensis) such as Kampung Permetang (KP), Kampung Pida-Tiga (KPT), Sungai Baru (SB1 and SB2), Kampung Pida-Empat (KPE), Singkir Yan (SY), Tanjung Dawai (TD), Dulang Besar (DB) and Kampung Bahagia (KB1 and KB2) were collected from paddy (Oryza sp.) growing areas in Kedah, Malaysia to identify resistant biotypes and their method of control. Weed biotypes were evaluated against all varying rates of propanil, quinclorac and cyhalofop-butyl. Except SY, all weed populations showed resistance against propanil at the rate of 5500 ml a.i. ha -1, on the contrary all weed populations appeared as susceptible against higher rates of propanil (11000 ml a.i. ha -1) except SB2 and KB1. All populations except KP and SB1 were resistant against cyhalofopbutyl at rates of 800 and 1600 ml a.i. ha -1. Kampung Bahagia (KB2) against cyhalofop-butyl at rates of 800 and 1600 ml a.i. ha -1 appeared as resistant and susceptible, respectively. Resistant biotypes were two times strongly resistant to propanil while one time strongly resistant to cyhalofop-butyl, respectively, than susceptible biotypes. Regardless of rates, quinclorac was ineffective against any of the biotypes. Resistant biotype SB2 was controlled by combined application of propanil and cyhalofopbutyl at rates of 5500 and 800 ml a.i. ha -1. Â© 2011 Academic Journals.